Development and validation of a green spectrophotometric method for simultaneous determination of combined pharmaceutical dosage form (paracetamol and caffeine) using chemometrics technique in comparison with HPLC - Alattab, Bushra; Alarbagi, Fares Abdullah; Almaqtari , Maher Ali; Alhuraishi, Entesar; Al-Maydama, Hussein (Eclética Química, 2024)
A green analytical method, a simple, fast, and cost-effective simultaneous spectrophotometric method using two chemometric techniques, the partial least square regression (PLS) and principal component regression (PCR), for determining a combination of paracetamol and caffeine in pharmaceutical formulations was developed. Pretreatment and separation steps are not required in the proposed method. For model construction and validation, various drug concentrations and instrumental spectra of 25 mixed solutions of paracetamol and caffeine were analyzed. The UV analysis of the prepared mixtures was recorded for a selected solvent blank in the wavelength range of 210-300 nm. The digitized absorbance was sampled at 0.2-nm intervals. R2 values of 0.9993 and 0.9994 assigned for the PLS of paracetamol and caffeine and 0.9995 and 0.9991 for the PCR of paracetamol and caffeine, respectively, exhibited greater prediction efficiencies. The obtained results were statistically compared with the results of the HPLC reference method. Concerning accuracy and precision, the statistical comparison revealed no significant differences between the suggested and reference HPLC approaches.